Compressive syndrome of internal jugular veins in multiple sclerosis: does it matter?. (March 2014) - Radak, Dj; Tanaskovic, S; Antonic, Z; Kolar, J; Aleksic, N; Ilijevski, N
Objectives: Condition known as chronic cerebrospinal venous insufficiency (CCSVI) is characterized by insufficient cerebral vein drainage in patients with multiple sclerosis (MS) and internal jugular vein (IJV), vertebral and/or azygos veins stenoses. However, external compression on the IJV was not clearly described as a potential cause of CCSVI. We aim to present a case of CCSVI in a patient with MS caused by bilateral IJV inverted valves combined with IJV external compression by carotid bulb. Methods: A 31-year-old female patient was admitted to our institute for IJV and vertebral veins morphological and haemodynamical assessment after being treated for MS for the last 14 years. Colour Doppler ultrasonography showed right IJV prestenotic dilation and inverted valves in both IJV. Computerized tomography angiography showed bilateral IJV compression by carotid bulb. Haemodynamical Doppler parameters showed that external IJV compression significantly contributed to CCSVI occurrence. Results: Bilateral IJV confluence percutaneous angioplasty (PTA) was done, and the patient was discharged for further neurological examination. Partial carbon dioxide pressure was significantly lower in the distal part of both IJV following PTA and oxygen saturation increased. Conclusion: In the case presented, PTA of the IJV confluence resulted in haemodynamic improvement despite the presence of IJV external compression.